PENGARUH JENIS KEMASAN TERHADAP MASA SIMPAN BAWANG DAUN - Subagyo, Ni Jeni Fanira; Handoko, Yoga Aji; Yulianingsih, Wamilia (Jurnal Sains dan Teknologi Pangan, 2021)
ABSTRACTThe Spring onion (Allium fistulosum L) is one of the vegetables that deserve intensive development, since it has high economic value and in Indonesia it is used as both a mainstay and a highly popular mix of food. The notable physical change of the leaf during the storage process is the change in leaf color, elegance, decay, and stupobility. Product destruction affects a degree of freshness during distribution because it cannot last long, so proper postposte treatment is required to reduce the rate of respiration of the spring onion after the harvest and other factors that can cause decline in quality. This study is aimed at figuring out the effect that packaging has on storing leeks and knowing the correct packaging for storing leeks. The method used was the heavy shrink measurement, the color and texture of the leaf. The experimental used was a Random design complete (RAL) design with 4 such treatments as unpacked treatment, kraft paper packaging, kitchen tissues and plastic wrap each 3 times the test. The spring onion is heavy with an average of 32.50% non-packaged treatment, paper kraft 45.61%, kitchen tissue 37.54% and plastic wrap 48.38%. A relatively small or slow change in color and texture change is the packing treatment used as a plastic wrap. Based on research conducted, it could be concluded that packaging has had a tangible effect on the storing of Spring onion. Wrap a plastic wrap that can extend the leeks' saving period, since Spring onion packed in plastic wrap shrinkage are relatively small, the color of the leaf and the texture of the bar do not easily wither and decay.Keywords: Spring onion, Packaging, Storage Period